Impact of road features on shared e-scooter trip volume: A study based on multiple membership multilevel model. (July 2022) - Yang, Hongtai; Bao, Yongxing; Huo, Jinghai; Hu, Simon; Yang, Linchuan; Sun, Lijun
Highlights: Effects of road features on e-scooter trip volume (ETV) of the segment are studied. The multiple membership multilevel model is used to tackle the boundary problem. Segments with sidewalks, dedicated bicycle facilities, and slower traffic are preferred. Density of street lights and trees are also positively related to ETV. ETV is higher in the commercial, residential, and high-income areas. Abstract: E-scooter sharing systems have been widely adopted by cities around the world. Previous studies analyzed community-level factors influencing e-scooter usage. Few studies examined the effect of road features on e-scooter trip volume (ETV) of the road segment, which can reveal the road features that riders prefer. This study explores this topic by analyzing the ETV of 29, 544 road segments in Calgary, Canada, while controlling for community-level factors. Because some segments are the boundaries of multiple communities, the multiple membership multilevel model is adopted to tackle this boundary problem. The results show that segments with sidewalks, dedicated bicycle facilities, lower speed limit, more street lights and trees have higher ETV. ETV is also higher in communities with high income, high percentage of commercial and residential area. Quantifying the effect of road features on ETV could help government agencies determine where e-scooters should be ridden and design road facility improvement plans for e-scooter users.